Phenolic composition of pomegranate peel extracts using an liquid chromatography‐mass spectrometry approach with silica hydride columns. Issue 7 (10th March 2017) - Young, Joshua E.; Pan, Zhongli; Teh, Hui Ean; Menon, Veena; Modereger, Brent; Pesek, Joseph J.; Matyska, Maria T.; Dao, Lan; Takeoka, Gary
Abstract : The peels of different pomegranate cultivars (Molla Nepes, Parfianka, Purple Heart, Wonderful and Vkunsyi) were compared in terms of phenolic composition and total phenolics. Analyses were performed on two silica hydride based stationary phases: phenyl and undecanoic acid columns. Quantitation was accomplished by developing a liquid chromatography with mass spectrometry approach for separating different phenolic analytes, initially in the form of reference standards and then with pomegranate extracts. The high‐performance liquid chromatography columns used in the separations had the ability to retain a wide polarity range of phenolic analytes, as well as offering beneficial secondary selectivity mechanisms for resolving the isobaric compounds, catechin and epicatechin. The Vkunsyi peel extract had the highest concentration of phenolics (as determined by liquid chromatography with mass spectrometry) and was the only cultivar to contain the important compound punicalagin. The liquid chromatography with mass spectrometry data were compared to the standard total phenolics content as determined by using the Folin–Ciocalteu assay.